Perancangan dan Implementasi Sistem Absensi Karyawan Berbasis Website untuk Meningkatkan Kecepatan dan Efisiensi Pengelolaan Kehadiran pada PT. Sembilan Cipta Karya - Gilang Anggara; Jeki Armentaria (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2026)
Organizations today increasingly rely on digital systems to support daily operational activities, including employee attendance management. Attendance systems are essential in human resource management because they are closely related to discipline, performance assessment, and company administration. At PT. Sembilan Cipta Karya, employee attendance is still recorded using fingerprint devices connected locally, so data processing remains offline. This condition causes delays in attendance recapitulation, limits access to information, and makes administrative data management less efficient. A web-based attendance system is therefore expected to record employee attendance in real time, simplify data management, and generate attendance reports more quickly and accurately, enabling the system to improve administrative efficiency and support management in monitoring employee attendance more effectively. This study aims to design and implement a web-based employee attendance system to increase the speed and efficiency of attendance data management. The research method used is Research and Development with a system development approach based on the waterfall model. The waterfall stages include requirements analysis, system design, implementation, testing, and evaluation. This research was conducted at PT. Sembilan Cipta Karya using observation, interviews, and documentation studies as data collection techniques. The results indicate that the web-based attendance system can record employee attendance in real time, simplify data processing, and provide downloadable data in Excel format for recapitulation needs. The system is also able to reduce the time required for recapitulation. Efficiency testing was conducted by comparing the processing time of attendance data between the previous system and the new system. The old system required approximately 60 minutes for daily recapitulation and 120 minutes for monthly reports, while the web-based system required only about 15 minutes for daily recapitulation and 30 minutes for monthly reports. Based on calculations using the efficiency formula, the system can save up to 75% of the time, showing that the developed system is more efficient than the previous one.